Correlation analysis between foot deformity and diabetic foot with radiographic measurement - Luo, Xu; Zhang, Chun; Huang, Qiuhong; Du, Zhipeng; Ni, Xia; Zeng, Qinglian; Cheng, Qingfeng (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background Foot deformity is a risk factor for diabetic foot ulcer. This study was aimed to investigate the relationship between hallux valgus (HV) and diabetic foot through the radiographic measurement. Methods The patients with diabetic foot hospitalizing in the Department of Endocrinology, the First Affiliated Hospital of Chongqing Medical University from September 2016 to June 2020 were selected. Then the foot plain X-ray radiographs were completed, and the size of HV angle (HVA) was measured. Their clinical data were collected, and the ulcer recurrence rate, amputation rate and mortality rate of the patients were followed up. Results A total of 370 patients were included. According to HVA, patients were divided into non-HV group (HVA<15°), and mild (15°≤HVA ≤ 20°), moderate (20°<HVA ≤ 40°) and severe (HVA>40°) HV groups. The age, height, BMI, smoking history and glycosylated hemoglobin level among the non-HVA, mild, moderate, and severe HV group (P<0.05), while smoking history, HbA1c, eGFR and autonomic neuropathy were significantly lower in HV group than those in non-HV group (P<0.05). The ulcer area in patients with moderate HV was larger than that in non-HV patients, and the severity of infection in patients with severe HV was significantly higher than that the other three groups (P<0.05). Conclusion The occurrence of HV is not only related to age and BMI, but also to the creatinine and eGFR level, autonomic neuropathy, lower limb arteriosclerosis occlusion, coronary heart disease and hypertension. Therefore, more attention should be paid to renal function screening, neuropathy screening and evaluation of lower extremity vascular lesions in patients with diabetes, especially those with moderate or higher HV.